Passage rate, phosphorus metabolism (32P) and body composition by tomography of lambs infected in single dose of Trichostrongylus colubriformis - Bompadre, Thiago Francisco Ventoso (2019)
The aim of this study was to identify physiological, biochemical and metabolic changes in sheep infected with T. colubriformis, and possible interaction with the deficient consumption of P. The animals were completely randomized distributed in four treatments, in a split-plot factorial arrangement 2×2, with two levels of P in the diet (sufficient and deficient) and two sanitary conditions with and without T. colubriformis. Eighteen Santa Ines lambs with initial body weight of 22.4 ± 2.7 kg, were distributed as: sufficient P content and uninfected (n = 4), deficient P and uninfected (n = 4), sufficient P content and infected (n = 5) and deficient P and infection (n = 5). Deficient P diet animals consumed 53% of P consumed by sufficient treatment. Infected lambs received 40,000 T. colubriformis in L3 larval stage in a single oral dose. For performance the animals were weekly weighed in fasting condition, and the apparent digestibility and methane emission were performed in individual metabolic stalls. Passage rate was determined with external (Yb, Co and Cr) and internal (iNDF) markers. The P metabolism was evaluated by the isotope dilution technique with 32P isotope. Ruminal liquid phase samples were used to determine short chain fatty acids, and urine samples to determine the microbial protein using the purines derivatives technique. Two computered tomography scans were performed to determine tissue density, one at the beginning of the experiment and one just before 32P injection. Histological analyzes were performed in the duodenal region, due to characterize mucosa modifications caused by the infection, methane determination was conducted in respirometric chambers. Blood hematological and biochemical parameters were tested twice a month throughout the experiment. Among the main results obtained, it was found that infection by T. colubriformis did not affect sheep consumption and performance. However, P and N metabolism were affected in infected animals, which presented lower absorption values (compatible with the mucosal lesions evaluated in histological trial) and plasma P concentration with higher turnover rate and lower bone density with lower P content in bones (P <0.05). Regarding N metabolism, infected animals presented lower retention with greater N loss via urine. Thus, it was concluded that acute T. colubriformis infection negatively affected P and N metabolism, and compromised sheep bone mineralization